Maintaining microbiota across diverse symbiotic organs in Euprymna scolopes : Insights into shared immune responses - Nidhi Vijayan; John Briseño; Oleg Simakov; Spencer V. Nyholm (Proceedings of the National Academy of Sciences, 2026)
Many animals have multiple organs or tissues that are colonized by diverse microbiota. The female Hawaiian bobtail squid, Euprymna scolopes , has two organs with distinct symbiotic communities: the accessory nidamental gland (ANG) and the light organ (LO). The ANG hosts a bacterial consortium, whereas the LO has a binary relationship with Vibrio fischeri , housed in extracellular crypt spaces as part of the central core (CC). To understand how the host maintains distinct symbiotic communities, we used transcriptomics to identify immune-related genes that are uniquely and similarly expressed in the ANG and LO-CC compared to organs without a known microbiota. Genes such as peptidoglycan recognition proteins EsPGRP2 and EsPGRP3, cathepsin-Z, alkaline phosphatase, and acidic phospholipase exhibited significant upregulation in the symbiotic organs compared to other tissues like gills, skin, mantle, optic lobe, ovaries, and brain. Moreover, EsPGRP2 displayed distinct localization patterns within the ANG, inversely correlating with bacterial presence, whereas the protein was colocalized with V. fischeri in the LO-CC. Notably, 10 different galaxins (EsGal) were uniquely highly expressed in both the ANG and LO-CC, with EsGal1 messenger RNA predominantly localized to the LO-CC epithelium, while EsGal2 and EsGal3 were primarily found in the epithelia of ANG tubules. Furthermore, antimicrobial assays using partial peptides derived from EsGal1 and EsGal2 showed varying and distinct patterns of inhibitory activity for these peptides. In summary, our findings identify similar immune gene families expressed across functionally distinct symbiotic organs in E. scolopes , suggesting that common immunomodulatory factors may maintain distinct symbiotic niches in the host.